A contrastive study of English and Vietnamese proverbs about moral values of family relationships / Nguyễn Đức Long; GVHD: Võ Đại Quang - Nguyễn, Đức Long
The thesis “A contrastive study of English and Vietnamese proverbs about moral values of family relationships” attempts to investigate syntactic and cultural features of English and Vietnamese proverbs about moral values of family relationships. The study is implemented via the adoptions of statistical, descriptive and contrastive, inductive, and deductive methods. The similarities between English and Vietnamese proverbs about moral values of family relationships are that both of them have subject which is a noun, pronoun, noun phrases and always precedes the verb in the sentence and the object in these two languages’ sentence can be a noun or noun phrase. It appears from the investigation of the English and Vietnamese proverbs that both societies emphasize the importance of moral values and treating the children, brothers and sisters and parents with great consideration. However, due to the collective nature of Vietnamese society, Vietnamese proverbs show that these relationships are more close and tight than those in English culture. It seems that Vietnamese proverbs are much more profound as they deal with the moral values in family. But, the English proverbs just tent to emphasize the important of women which are as essential as that of men